Effect of different microbial seeds on batch anaerobic digestion of fish waste - Abu Hanifa Jannat, Md; Hyeok Park, Sang; Chairattanawat, Chayanee; Yulisa, Arma; Hwang, Seokhwan (Bioresource technology, 2022)
[Display omitted] •Investigation of batch AD of fish waste (FW) using different microbial seeds.•Seed from digester co-digesting manure and food waste found most suitable for FW.•Highest CH4 yield of 350.5 ± 5.2 mL/gVSadded obtained by best performing seed.•Dominance of Methanosaeta in the initial seed contributed to higher CH4 yield. Initial microbial compositions would be the precursor for the efficient anaerobic digestion (AD) of fish waste (FW). A mesophilic batch test was conducted using four seeds collected from different digesters treating various combinations of substrates to investigate their effects on FW degradation. Key microbial groups were identified by 16s rRNA gene-based metagenomics analysis. Among four, the seed from the digester co-digesting livestock manure, food waste, and food wastewater showed the best performance and obtained the highest methane yield (350.5 ± 5.2 mL/gVSadded) and lowest lag phase (0.6 ± 0.1 d). Proteiniphilum, Aminobacterium, dgA-11 gut group, and Syntrophomonas were dominant bacterial genera identified in FW degradation. Methanosaeta was the dominant methanogen in the best performing seed and microbial network analysis revealed its contribution to achieving the highest CH4 yield. Obtained results could be useful in selecting microbial seed sources to avoid system imbalance in full-scale digesters that treat FW.